(3QSGdI aj GdaYd hGdEfaYGd hCbSGegeGs - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s
(3ChdgG (B:s
(3EYde Cf GdCaYGd hGdEfaYGdGJ jJaGhJ HMSH JaGQJ GdGehQ GdYbdjI GdfaSGfjI efgG hGdLSeGfjI aeG Pdc Cfg cdeG cGf GdTF Cbhi hCJe ef ZjQg s
(3BNQgG (B:s
(3hGdEHGfI ef cd Yde efgG HbhGfjfgG GdcdjI hGdeSGFd GdLRFjI hdcf GdYPQ ai GdEeSGc Yf JaGUjdgG hGVM hYfOFP fNJe GdQSGdI hGdMeO dhGgH GdYbd s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG CQVg , JQeje s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdadSaI hGdefWbs